The relationship between the distance learning education and language skills development in the applied linguistics in English program for students attending the eighth level of the army polytechnic school, during the term October 2008 march 2009 - Cajamarca Peñaranda, Guillermo (2009)
In today s increasingly interconnected world, knowledge of more than one language is quickly becoming a necessary and crucial skill for the workplace. It is vital to be able to know, understand and be fluent when communicating each other through the use of a new language. That is why most countries around the world have resolved and embraced English as a foreign language that in turn would better and break down the walls of communication as it often occurs in economics, education, commerce, and media. In view of that, those who have decided to learn and adopt English as a foreign language, have to know and be able to use its four basic skills: listening, speaking, reading and writing, which are connected each other by means of two parameters: 1) Mode of Communication (Spoken or Written message) and 2) Direction of Communication (Input: listening-reading message or Output: speaking-writing message), carried out by means of the practice. As previously mentioned above, and after having finished our career in Applied Linguistics in English Program, we consider that the Distance Learning Education does not leave room for carrying out this task properly so as to have a good evenly command of these abilities mainly due to lack of practice especially that of Listening and Speaking skills.